A systematic investigation on microstructure evolution, phase transformation and dynamic recrystallization mechanisms of hot isostatic pressed Ti–45Al–2Mn–2Nb–1B alloy during hot deformation - Meiyi Ba; Hongkui Tang; Lianxi Hu; Yu Sun; Fei Gao (Journal of Materials Research and Technology)
A titanium aluminum alloy (Ti–45Al–2Mn–2Nb–1B, at%) was prepared using hot isostatic pressing (HIP). Thermal simulation compression were carried out at an elevated temperature of 1100–1250 °C, strain rate between 0.001 and 1 s−1, and a reduction in height of 50%. The thermal deformation behaviors, microstructural evolution, and dynamic recrystallization (DRX) mechanisms were investigated. The results show that stress-induced phase transformation from γ (L10) to α2 (hcp) is facilitated through the successive glide of a/6 [11-2] Shockley partial dislocations across alternating {111} planes of γ phase. The DRX were analyzed using Geometrically necessary dislocations (GND). In the α + γ phase region, the DRX becomes more abundant at an increase in temperature to 1250 °C and a decrease in strain rate to 0.001 s−1. The misorientation analysis showed that continuous dynamic recrystallization (CDRX), which occurs through subgrain rotation and misorientation accumulation, weakens at elevated temperatures and low strain rates. However, discontinuous dynamic recrystallization (DDRX), characterized by the dominance of strain-induced boundary migration mechanism (SIBM) and bulging nucleation, develops more extensively under the same parameters. The microstructure after thermal deformation contains true twins (TT) and pseudo twins (PT) and the DRX grains near twin boundaries (TBs) show a peak misorientation angle of 89 ± 3°, driven by high strain energy at twin intersections. Among the various DRX mechanisms, DDRX emerges as the dominant. This comprehensive analysis offers novel insights into DRX mechanisms, providing valuable guidance for optimizing the hot working process of Ti–45Al–2Mn–2Nb–1B (at%) alloy.